1989
DOI: 10.1093/nar/17.15.6393
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the quailc-junprotooncogene

Abstract: The c-jun protooncogene is a member of a multigene family of transription factors with leucine zipper which also includes jun B and jun D/S 1,2 . The protein complex c-jun/c-fos has been shown to be responsible for the so-called AP1 (human)/PEA1 (murine) transcription factor *To whom correspondence should be addressed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Immunoprecipitation with polyclonal antisera directed against recombinant Jun or Myc proteins or against Gag-related proteins was carried out with extracts from cells used for the Northern analyses shown in Figure 1. The analyses shown in Figure 2 revealed that normal QEF, QEF transfected with the empty RCAS retroviral vector, CEF or CEF infected with NK24, contained the normal low levels of endogenous quail or chicken c-Jun (313 amino acids, M r 34 341, or 310 amino acids, M r 33 940) (Brun et al, 1989;Nishimura and Vogt, 1988) or endogenous quail c-Myc (417 amino acids, M r 46 236) proteins with gelelectrophoretic mobilities corresponding to apparent molecular weights of 42 000 and 52 000, respectively. QEF transformed by the RCAS ± CJ3 or RCAS ± VJ1 constructs contained high levels of retrovirally speci®ed c-Jun (328 amino acids, M r 35 880, apparent molecular weight 42 000) or v-Jun (295 amino acids, M r 32 314, apparent molecular weight 36 000) proteins ( Figure 2A).…”
Section: Bkj Activation In ®Broblasts Is Also Induced By V-fosmentioning
confidence: 99%
“…Immunoprecipitation with polyclonal antisera directed against recombinant Jun or Myc proteins or against Gag-related proteins was carried out with extracts from cells used for the Northern analyses shown in Figure 1. The analyses shown in Figure 2 revealed that normal QEF, QEF transfected with the empty RCAS retroviral vector, CEF or CEF infected with NK24, contained the normal low levels of endogenous quail or chicken c-Jun (313 amino acids, M r 34 341, or 310 amino acids, M r 33 940) (Brun et al, 1989;Nishimura and Vogt, 1988) or endogenous quail c-Myc (417 amino acids, M r 46 236) proteins with gelelectrophoretic mobilities corresponding to apparent molecular weights of 42 000 and 52 000, respectively. QEF transformed by the RCAS ± CJ3 or RCAS ± VJ1 constructs contained high levels of retrovirally speci®ed c-Jun (328 amino acids, M r 35 880, apparent molecular weight 42 000) or v-Jun (295 amino acids, M r 32 314, apparent molecular weight 36 000) proteins ( Figure 2A).…”
Section: Bkj Activation In ®Broblasts Is Also Induced By V-fosmentioning
confidence: 99%
“…Charged decays of the kaon were simulated with Geant4 [5] [6]. A list of selection criteria was sequentially applied to each event in the resulting Root [7] file. Events were eliminated if any of the following were true: a charged particle or photon was detected by the LAVs, IRC, or SAC; fewer than two energy clusters were detected by the LKr (clusters closer than 6 cm were merged); the reconstructed π 0 decayed outside of the fiducial region (105 < z < 155 m); an LKr cluster was closer than 35 cm to the beamline center; or the transverse momentum of the reconstructed π 0 was less than 0.12 GeV/c.…”
Section: Simulation and Analysismentioning
confidence: 99%